Application of GIS and RS in Tourism: Case study: Sulaimaniyah Province, Kurdistan Region, Iraq - Azeez, Salim Neimat; Rahimi, Iraj; Ahmed, Imran Hassan (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
As one of the most significant economic sectors, tourism can create numerous job opportunities and generate significant development almost worldwide. To expand the tourism industry, new technologies play an essential role that should be taken into consideration. Geographic Information Systems (GIS) and Remote Sensing (RS) are two of the main aids helping the tourism industry. During recent years, the Sulaimaniyah Governorate of the Kurdistan region of Iraq (KRI) has hosted of hundreds of thousands of tourists from Iraq’s middle and southern parts. In the KRI, political and security situations accompanied by numerous natural attractions with pleasant weather conditions have motivated the Iraqi tourists to travel and even settle in the KRI. This study aimed to utilize the GIS/RS techniques to produce some accurate maps and information, using statistical tourism-related data and satellite data, that could be used for decision making and planning in the tourism industry. The used method focuses on creating needed spatial information layers then overlayping them in a sort of single maps to display spatial distribution of different touristic information which helps managers and users to interprete and analyse current situation more easily. This study displayed how GIS/RS can provide helpful information in tourism planning and development. The created maps showed that Sulaimaniyah suffers from a lack of highways and the unbalanced geographical distribution of hotels and tourist facilities. Produced maps also showed that there are only three short highways exist in the city. On the other side, the spatial distribution of hotels hardly follows the distribution of most visited attractive spots.The only well-organized facility that can meet the tourism demand, to a high degree, are restaurants. The results also revealed that visitors’ distribution during the spring and summer seasons is not following the same pattern. During spring, tourists are mostly inclined to visit well-organized, attractive spots and natural, accessible attractions. In summer, the accessible higher elevation spot with better weather conditions (e.g., Hawraman, Sitak, Qandil) has been more interesting for local tourists or from the south and middle parts of Iraq.